Perbandingan Harga Saham, TVA Dan Abnormal Return Sebelum Dan Sesudah Stock Split - Mustofa, Moch. Sa'dun; Widodo, Agustina (Universitas Islam Kadiri, 2024)
This study aims to determine the differences in stock prices, trading volume activity and abnormal returns before and after the stock split event in companies listed on the Indonesia Stock Exchange with a time span of 2019-2023. Sampling in this study used purposive sampling, with data obtained from 47 observation companies. The parametric test used was the paired sample t-test. The results of the partial test (paired sample t-test) showed no significant difference in the trading volume activity variable in the test 10 days before and 10 days after the stock split event. However, the stock price and abnormal return activity variables showed a significant difference in the test 10 days before and 10 days after the stock split event.